Tatalaksana Nonbedah Pada Penyempitan Pembuluh Darah Utama Koroner Kiri yang Terisolasi - Kabul Priyantoro; Sunarya Soerianata (The Indonesian Heart Association, 2012)
Prevalence of Left Main Coroner Artery (LMCA) stenosis inpatients undergoing coronary angiography was 2.5 to 10 %, almosrt all patients suffer from concomitantatherosclerotic disease of other coronary branches. Incontrast, an isolated atherosclerotic lesion of LMCA is very rare. with iscidences 0.07 to 0.15 %. Coroner artery by pass graft surgery (CABG) has been recommended as the standard treatment in LMCA disease, however, percutaneous coronary interventions (PCI) on the LMCA remained in scope, as some patients with high risk or contra indications of CABG and very limited life expectancy, still had no other option than PCI.A 58th years old man with factor; smoker, dyslipidemia and hypertention, complain of chest discomfort, he was referred with diagnosis of APS CCS III and MSCT coroner revealed mild plaque burden with critical subtotal occlusion i n in LMCA, calcified plaque in LAD and other vessels were normal. He refuse CABG and went for PCI, angiography revealed significant isolated unprotected LMCA disease. Successful PCI using anchor wire technique and implantation of BMS in the lesion was done. Patient discharged on day 6 of hospitalization with no complication.